Half Antiperovskites VI: On the Substitution Effects in Shandites InxSn2–xCo3S212. Issue 2 (9th January 2014) - Pielnhofer, Florian; Rothballer, Jan; Peter, Philipp; Yan, Wenjie; Schappacher, Falko M.; Pöttgen, Rainer; Weihrich, Richard
Abstract: In the shandite type solid solution In x Sn2– x Co3 S2 the transition from half metal ferromagnetic Sn2 Co3 S2 to the new thermoelectric InSnCo3 S2 is related to A = In, Sn on different crystallographic sites. Effects and origin of crystal and electronic structure changes induced by A = In are now investigated within the solid solution 0 ≤ x ≤ 2 including In2 Co3 S2 . Effects are studied from X‐ray data, 119 Sn Mößbauer spectroscopy, and ab initio calculations. Their origin is explored by DFT modeling on site preference of In and Sn in a supercell, electric field gradients (EFG), spin polarization, band structures, and direct space analyses (ELF, AIM). Indium is found to cause the crystal structure distortion on one A site, the electronic structure distortion to the other, as a consequence of inverted anisotropic bonding. Abstract :